Coreopsis: A Guide To Identifying and Enjoying Florida's State Wildflower - Jeff G. Norcini; Melissa A. Thorpe (EDIS)
In this pamphlet, general information is provided about flowering, life cycle, abundance, and the types of habitat in which tickseeds grow in Florida. This information refers to naturally occurring populations, except where noted.